A Spectrum of Neural Tube Defects: An Observational Study in the Eastern State of India - Kumari B, Shanta; Baisakh, Pratima; Bhat, Vinayak Ganesh; Pradhan, Sujita; Panda, Dhiren Kumar (South Eastern European Journal of Public Health, 2024)
Objective: This study aimed to determine the prevalence and types of neural tube defects (NTDs) in eastern India, examine the associated maternal and paternal risk factors, and evaluate the impact of antenatal ultrasonography for early detection and management. Materials and Methods: A four-year observational study was conducted at the IMS and SUM Hospital, SOA University, Bhubaneswar, India, from July 2020 to June 2024. Pregnant women attending the antenatal clinic were screened for NTDs by using high-resolution ultrasonography. Diagnosed cases were further confirmed by postmortem autopsy, when available. Relevant maternal and paternal demographic data, including age, socioeconomic status, consanguinity, body mass index (BMI), hyperthermia, and paternal occupation, were collected. Statistical analysis was performed using Fisher’s exact test to identify significant associations between these factors and NTD occurrence, with significance set at P < 0.05. Results: The incidence of NTDs was 9.12 per 1000 deliveries, with spina bifida (43.4%) being the most prevalent, followed by anencephaly (32.9%), and encephalocele (11.1%). NTDs were significantly associated with maternal age (20-24 years), lower socioeconomic status, consanguinity (12.93% of cases), maternal obesity (BMI ≥30 kg/m²), and hyperthermia (≥100 °F). Fathers engaged in labor-intensive occupations had higher rates of offspring with NTDs (56%). This study highlights the effectiveness of antenatal ultrasonography for early detection and management, particularly in high-risk populations. Conclusion: NTDs continue to pose a significant public health challenge in Eastern India. This study underscores the need for improved prenatal care, genetic counseling, and targeted public health interventions, including folic acid supplementation and lifestyle modifications, to mitigate risk factors. Future research should focus on expanding geographic coverage and integrating genetic analysis to better understand the complex interplay between environmental and genetic factors contributing to NTDs.